Decoupling of arch action and truss action in deep beams by strain energy. (August 2020) - He, Zhi-Qi; Xu, Tian; Liu, Zhao
Abstract: It is commonly accepted that deep beams transfer shear forces through a combination of arch action and truss action, but there is disagreement on how to estimate the fraction transferred by each assumed action. This study provides a theoretical method to decouple the two shear-carrying mechanisms from the perspective of strain energy. Through multiple-level least-energy solutions, a two-panel truss consisted of parallel compression diagonals and orthogonal tension ties is obtained for the minimum strain energy. Assuming that vertical ties of the truss model and diagonal ties of the combined model have the same energy, the fraction of load transferred by the truss action is decoupled as 2 λ /3–0.5 (where λ is the shear span-depth ratio). It means that the entire shear is carried by the arch action when λ  ≤ 0.75, while the entire shear is carried by the truss action when λ  ≥ 2.25. Six deep beams were tested with instruments placed along the assumed direct struts and indirect struts, from which the contributions of the two load-transfer mechanisms can be separated experimentally. The theoretical method agrees well with the experimental results of the current study and the others collected from the literature.